Research Progress on the Inflammatory Effects of Long Non-coding RNA in Traumatic Brain Injury - Wang, Jian-peng; Li, Chong; Ding, Wen-cong; Peng, Gang; Xiao, Ge-lei; Chen, Rui; Cheng, Quan (Frontiers in Molecular Neuroscience, 2022)
Globally, traumatic brain injury (TBI) is an acute clinical event and an important cause of death and long-term disability. Because the pathological mechanism of TBI secondary craniocerebral injury is complicated, multi-factors, and heterogeneity, the clinical treatment effect is often poor, It also brings a huge burden to individuals, families and society. Several studies have shown that lncRNAs are abundant in the central nervous system and participate in a variety of pathophysiological processes. Including oxidative stress, inflammation, apoptosis, blood-brain barrier protection, angiogenesis and neurogenesis, etc. Analysis of the related inflammation, immunity, and apoptosis pathways mediated by lncRNA after TBI has special significance for the treatment of TBI. This review discusses the differential expression of different lncRNAs in brain tissue after TBI, which may be related to the physiological and pathological process after TBI. These findings may also provide new targets for further research on the molecular mechanisms of TBI and potential therapeutic interventions.